2023
DOI: 10.3390/nu15112466
|View full text |Cite
|
Sign up to set email alerts
|

To Eat or Not to Eat—A Qualitative Exploration and Typology of Restrictive Dietary Practices among Middle-Aged and Older Adults

Lena Bandelin-Franke,
Liane Schenk,
Nadja-Raphaela Baer

Abstract: Favorable diets often include restrictive practices that have proven health benefits, even if initiated later in life. The aim of this qualitative study is to gain a comprehensive understanding of Restrictive Dietary Practices (RDPs) among a sample of middle-aged and older German adults (aged 59–78 years). We conducted 24 narrative in-depth interviews and analyzed the data using qualitative content analysis (Kuckartz). Following an inductive thematic approach, a typology was reconstructed comprising four typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…It appears vital to embed the above-mentioned difficulties with (re-)learning IS and thus IE in a broader societal context: whether for health or ethical reasons, there is a widespread trend of eating according to various kinds of restriction rules. This concerns several types of restrictive dietary practices [ 66 ], for instance, regarding specific foods or macronutrients (e.g., low-calorie diet [ 67 ] or temporal restrictions (e.g., fasting [ 68 ]). Data from a German population-wide consumption study showed that people are dieting more frequently as they age, with around 20% of people over 65 doing so [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…It appears vital to embed the above-mentioned difficulties with (re-)learning IS and thus IE in a broader societal context: whether for health or ethical reasons, there is a widespread trend of eating according to various kinds of restriction rules. This concerns several types of restrictive dietary practices [ 66 ], for instance, regarding specific foods or macronutrients (e.g., low-calorie diet [ 67 ] or temporal restrictions (e.g., fasting [ 68 ]). Data from a German population-wide consumption study showed that people are dieting more frequently as they age, with around 20% of people over 65 doing so [ 69 ].…”
Section: Discussionmentioning
confidence: 99%